Homozygous southeast asian hereditary ovalostomatocytosis: Management dilemma - Asnawi, AWA; Sathar, J; Nasir, SFSM; Mohamed, R; Jayaprakasam, KV; Vellapandian, ST (Wiley-Blackwell, 2024)
Indexed by WOS/SCOPUS